Demographic Profile of Traumatic Spine Injuries at a Level 1 Trauma Center of Eastern India: A Retrospective Study - Tiwari, Varun; Sadique, Shahid Iftekhar (Indian Journal of Neurotrauma, 2024)
Background Trauma is a leading cause of hospitalization worldwide, with spinal injuries resulting from traumatic events having severe and lasting repercussions. The high incidence of these injuries places a significant burden on families and health care systems. Disparities in epidemiological findings often occur due to the location- or culture-specific factors. This study aims to address the inadequate attention given to morphological patterns and their impact on neurological damage severity, which affects functional outcomes over time.Objectives The main objective of this study was to identify the injury patterns and detect associated spinal or extraspinal injuries in traumatic spine injury (TSI) patients who visited a level 1 trauma care facility in eastern India. Additionally, it aimed to establish a correlation between the severity, morphology, and grades of neurological damage with demographic characteristics.Materials and Methods This retrospective cross-sectional study was conducted at the neurosurgery unit of the trauma and emergency department (TED) at a level 1 trauma center in eastern India. It involved TSI patients admitted between March 15, 2023, and March 14, 2024. Data were collected from paper-based records and compiled into a structured Excel format. The study included adult patients admitted to the TED with traumatic spinal cord injuries and excluded those from outpatient departments or those with incomplete data. Data analysis utilized the Muller AO classification, Injury Severity Score (ISS), and ASIA classification, with statistical analysis performed using IBM SPSS version 19.0.Results Out of 320 patients, 309 met the inclusion criteria. The majority were males (263) with a median age of 39 years. Falling from a height (43.7%) was the most common mechanism of injury, followed by road traffic accidents (37.9%). Polytrauma was present in 73% of patients, with multilevel injuries more severe than single-region injuries. Type A fractures were most common (53.4%), and 67.6% of patients underwent surgery. A significant correlation was found between the ISS and ASIA scores.Conclusion The study revealed differences in spinal injury epidemiology in eastern India compared to other regions, with multiple vertebral level injuries being more common. The findings highlight the need for government health care strategies focused on treatment and rehabilitation, especially for the younger age group that is predominantly affected. Preventive measures should also be strictly enforced to reduce the incidence of such injuries.
Keywords: American Spinal Injury Association (ASIA) classification; eastern India; epidemiology; level 1 trauma center; morphological patterns; neurological damage; polytrauma; road traffic accidents; traumatic spine injuries